Using open source data to estimate the global epidemiology of pertussis - Haley Stone; Aye Moa; C Raina MacIntyre; Abrar A Chughtai (University of New South Wales, 2020)
Introduction: Pertussis is a highly infectious disease that remains endemic despite a rising vaccination coverage rates globally. Due to the lack of global surveillance data for pertussis, the unconventional use of open-source data gives a glimpse into global outbreaks, compensating for the lack of national reporting systems in some countries. The objective of the study is to describe global reporting of pertussis through open source data. Methods: An open-source database, EpiWATCH was used to analyse global outbreaks of pertussis. Data was retrieved on pertussis and analysed on multiple epidemiological factors from 2016 to 2019. In addition, prevalence rates were calculated for each country and compared to the World Health Organization (WHO) public domain data on global reported cases. Results: A total of 96 reports were collected globally between the years 2016 to 2019. Of those reports, 95.8% (92/96) were from high-income countries. Data from the United States comprised 59.3% (57/96) of the total reports. . In addition, prevalence rates were calculated for each country and compared to the World Health Organization (WHO) public domain data on global reported cases. An outbreak report was identified in Papua New Guinea, which was not reported in WHO surveillance. Discussion: Open-source data gives insight and analysis on pertussis outbreaks globally, given there is no formal global surveillance system for pertussis. There is a bias toward reports from high income countries in open source data. However, the timeliness of reporting coupled with assisting countries with lacking national reporting systems are benefits of open source data.